2022
DOI: 10.1080/10106049.2022.2074147
|View full text |Cite
|
Sign up to set email alerts
|

Influence of AGL flight and off-nadir images on UAV-SfM accuracy in complex morphology terrains

Abstract: In the field of geosciences and engineering, situations arise where special attention have to be paid to the planning of the UAV-photogrammetric project, i.e., terrain with complex geometry and steep slopes. The use of off-nadir imagery and flights at a fixed height above ground level (AGL) are postulated as possible factors to be considered to achieve high accuracies. The objective of this study is to evaluate the influence of image angle, frontal and side overlaps, and type of flight (above mean sea level (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…We provide more insights into image collection strategies than traditional overall accuracy indexes, such as RMSE. Previous studies have confirmed that oblique photography with a larger angle can effectively reduce elevation error [24,25]. The experimental results presented in this paper support this finding.…”
Section: Camera Angle Flying Height and Combination Strategiessupporting
confidence: 88%
See 1 more Smart Citation
“…We provide more insights into image collection strategies than traditional overall accuracy indexes, such as RMSE. Previous studies have confirmed that oblique photography with a larger angle can effectively reduce elevation error [24,25]. The experimental results presented in this paper support this finding.…”
Section: Camera Angle Flying Height and Combination Strategiessupporting
confidence: 88%
“…For consumer UAVs, studies have shown that multiple flight lines by flying in a "double-grid" (two orthogonal blocks) or nadir images supplemented with convergent images can achieve similar results to that of using a five-lens tilt camera. Furthermore, using higher overlap and higher oblique camera angles (20-35 • ) can effectively improve the overall accuracy of terrain modeling for consumer UAVs [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the 3D reconstruction was available at this step. The accuracy is expressed as the discrepancy between the measured and reconstructed coordinates of GCPs; this option is commonly accepted in the absence of validation points [54,65,102]. The values are shown in Table 3.…”
Section: Data Processingmentioning
confidence: 99%
“…SfM photogrammetry requires metric references in order to georeference the obtained results; to this aim, ground control points (GCPs) or RTK UAVs can be used. The overall quality of the obtained 3D reconstructions can be affected by the overlap between the images, image resolution, the geometry of acquisition, the numerosity and distribution of GCPs, and the accuracy of their coordinates [60][61][62][63][64][65]. UAV photogrammetry can be effectively applied in small-medium extension areas (a few tenth of a Ha) with low-sparse vegetation; it is suited for volume computations and surface deformation controls [66].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that although mass data collection methods are currently very popular in many fields of research involving complex terrain [26], such as coastal monitoring [27][28][29], volcano exploration [30], underground research [31,32], tree detection [33,34], the evolution of rock glaciers [35], monitoring of rock masses [36][37][38], or their geological analysis [39], vegetation filtering in such cases is typically handled by human operators as the performance of automated algorithms proposed for this purpose, so far, is generally poor as confirmed by Blanco et al [6]. Specifically, they usually have problems when encountering highly rugged and/or sloped terrain [15].…”
Section: Introductionmentioning
confidence: 99%